FIGHTS AT SCHOOL: TEACHING STRATEGIES OF PHYSICAL EDUCATION TEACHERS - Marcos Paulo Vaz de Campos Pereira; Alcyane Marinho; Larissa Rafaela Galatti; Alcides José Scaglia; Gelcemar Oliveira Farias (Journal of Physical Education)
ABSTRACT This study aimed to identify the teaching strategies of Physical Education teachers to address fights as a content in the school context. A total of 77 Physical Education teachers from state schools in the Greater Florianópolis Region participated in the descriptive research. A questionnaire was used for data collection. The results showed that the teachers were not used to teaching fights, and identified as strategies a teaching centered on motor exercises, fight modalities, technique demonstration, capoeira and games. It can be concluded that the teaching of fights in the investigated context is scarce, as only 18 teachers addressed them in their classes. It is possible to observe the mediation of the teachers in using their strategies to provide this content to their students. It can be concluded that few teachers address the fights content, since the findings reveal the scarcity of this approach, pointing to a disconnection between fights and the school context.